THE RELATIONSHIP BETWEEN LEADERSHIP, MOTIVATION, AND WORK DISCIPLINE WITH EMPLOYEE PERFORMANCE (STUDY ON PERUM. BULOG KANWIL LAMPUNG) - Auni, Mithalina; Aprilani, Deddy; Nugeraha, Prasetya (Jurnal Kompetitif Bisnis, 2024)
The work directly associated with the strategic goals implemented by the company determines employee performance. Therefore, obtaining a profound understanding of the aspects influencing employee performance is crucial. The aim of this research is to provide a comprehensive study on the influence of leadership, motivation, and work discipline on employee performance at the Regional Office of the National Logistics Agency (BULOG) in Lampung. This research uses an explanatory approach with a quantitative research method. The research subjects in this study consist of all employees of Perum. Bulog Kanwil Lampung, totaling 57 individuals, using the cluster sampling technique. The obtained data were then analyzed using multiple linear regression analysis. The research findings indicate that leadership does not have a significant impact on employee performance, but motivation and work discipline have a highly significant influence on employee performance at Perum. These results have important implications for management in human resource utilization and organizational performance improvement. Recognizing the importance of work discipline in enhancing employee performance is crucial for designing more efficient strategies in workforce management within the company's environment.